Integrating Spatial Planning and Agroecology to Enhance Agricultural Carrying Capacity in Rural Development Zones - Rince Tambunan; Ummy Kalsum; Muh. Nur (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Spatial planning has been recognized as a critical tool for guiding regional development in alignment with environmental conservation and food security objectives. However, in practice, discrepancies often exist between formal spatial planning and adaptive, locally-based agricultural systems. This gap creates a knowledge divide in understanding how spatial and agroecological aspects can be synergistically integrated to support the sustainability of agricultural areas. This study aims to explore the integration of spatial planning and agroecology practices to enhance the carrying capacity of agricultural zones within rural development areas. The research employs a qualitative approach with a sequential explanatory design, beginning with in-depth interviews with local stakeholders in North Konawe Regency. The findings indicate that strengthening the carrying capacity of agricultural areas requires a more contextual integration between spatial planning policies and community agroecological practices, which, in turn, enhances the effectiveness of regionally-based development planning. These results have theoretical implications for expanding the understanding of the interrelationship between spatial planning and agroecology, as well as practical implications for formulating policies that leverage local potentials to achieve sustainable rural development.